A Microfluidic System for Studying the Effects of Disturbed Flow on Endothelial Cells - Tovar-Lopez, Francisco; Thurgood, Peter; Gilliam, Christopher; Nguyen, Ngan; Pirogova, Elena; Khoshmanesh, Khashayar; Baratchi, Sara (Frontiers in Bioengineering and Biotechnology, 2019)
Arterial endothelium experience physical stress associated with blood flow and plays a central role in maintaining vascular integrity and homeostasis in response to hemodynamic forces. Blood flow within vessels is generally laminar and streamlined. However, abrupt changes in the vessel geometry due to branching, sharp turns or stenosis can disturb the laminar blood flow, causing secondary flows in the form of vortices. Such disturbed flow patterns activate pro-inflammatory phenotypes in endothelial cells, damaging the endothelial layer and can lead to atherosclerosis and thrombosis. Here, we report a microfluidic system with integrated ridge shaped obstacles to generate controllable disturbed flow patterns. This system is used to study the effect of disturbed flow on the cytoskeleton remodelling and nuclear shape and size of cultured human aortic endothelial cells. Our results clearly demonstrate that the generated disturbed flow changes the orientation angle of actin stress fibres, reduces the nuclear size while increases the nuclear circularity.